A 5 years old female child recovered from Moyamoya Disease with Unani formulation: A Case Report - Md. Shafat, Karim; Fauzia, Khatoon; Firoz, Wasim; Mohd., Zulkifle (International Journal of Medical Practitioners, 2023)
Moyamoya disease is a very rare chronic circulatory occlusive disorder of the blood vessels of the brain, in which patients complain of headache, seizure, weakness, and sometimes paralysis. A 5 years old female child with a complaint of headache and seizure was admitted elsewhere and during the treatment, she was diagnosed with Moyamoya disease. Further, she went to AIIMS Patna, where the neurosurgeon advised Digital Subtraction Angiography (DSA) and after the final diagnosis, they suggest the surgical intervention of the brain. During the search for an alternative treatment, they consulted my center for Unani treatment. We advised a semiliquid Unani polyherbal formulation containing Gule Banafsha (Viola odorata), Ustukhuddoos(Lavandula stoechas), and Nilofer (Nymphaea alba Linn) for three months. After the completion of the treatment schedule, she went for DSA again in Patna AIIMS and they find that there is no sign of occlusion in the blood vessels of the brain. The patient has no complaints and the report also showed that she gets improved.
Keywords: Moyamoya; Unani; Ustukhuddoos (Lavandula stoechas); Nilofer (Nymphaea alba Linn); Gule Banafsha (Viola odorata).